Revision of the crassipes and pictipes species groups of Apiomerus Hahn (Hemiptera: Reduviidae: Harpactorinae) - Berniker, Lily; Szerlip, Sigurd; Forero, Dimitri; Weirauch, Christiane (Zootaxa, 2011)
Within the genus Apiomerus Hahn, 1831, the crassipes and the pictipes species groups are described. In the crassipes species group, three species are redescribed: Apiomerus crassipes (Fabricius, 1803), Apiomerus rufipennis (Fallou, 1889) and Apiomerus spissipes (Say, 1825); one subspecies is raised to species level and redescribed: Apiomerus cooremani Costa Lima, Campos Seabra & Hathaway, 1951; and six species are described as new: Apiomerus californicus Berniker & Szerlip, sp. nov., Apiomerus cazieri Berniker & Szerlip, sp. nov., Apiomerus floridensis Berniker & Szerlip, sp. nov., Apiomerus montanus Berniker & Szerlip, sp. nov., Apiomerus peninsularis Berniker & Szerlip, sp. nov. and Apiomerus wygodzinskyi Berniker & Szerlip, sp. nov. In the pictipes species group, two species are redescribed, Apiomerus flaviventris Herrich-Schaeffer, 1846 and Apiomerus pictipes Herrich-Schaeffer, 1846, and one subspecies, Apiomerus pictipes pittieri Costa Lima, Campos Seabra, & Hathaway, 1951 is synonymized with Apiomerus pictipes. Neotypes are designated for Apiomerus flaviventris, Apiomerus pictipes, and Apiomerus spissipes. Lectotypes are designated for Apiomerus cooremani and Apiomerus crassipes. The composition of the species groups are different from those originally proposed by Sigurd Szerlip in his PhD dissertation. The crassipes group has one additional member, Apiomerus rufipennis. Furthermore, Apiomerus barrocoloradoi Forero, Berniker & Szerlip, 2010 and the two manuscript names “Apiomerus panther” and “Apiomerus tigris” were removed from the pictipes group. A key to the species is provided, as well as photographs of habitus and diagnostic features for both males and females. Intraspecific polychromatism is discussed as it relates to species identification and species delimitation.